2022
DOI: 10.1039/d1cp02044g
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the radicaloid character of polyaromatic hydrocarbon couplers on magnetic exchange interactions

Abstract: The molecular properties of the conjugated spacers, such as the π-conjugation, aromaticity, length of the couplers, etc., that couple two localized spin-centers influence the intramolecular magnetic exchange interactions (2J) mediated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…This is well reflected from the 〈 S 2 〉 BS values (Table S5 in ESI†) exceeding 1.0 from n = 8 onward, indicating the contribution from the components of higher spin multiplicities and hence reflecting the multi-configurational character. 29,76 The fractional occupation numbers of BS-UHF based natural orbitals (Table S7 of ESI†) used to compute the radicaloid character, further support the idea of tetra-radical character, with four nearly singly occupied open shells from n = 11 onwards. A DMRG study by Chan et al also established the singlet diradical ground state with the plausible evolution of polyradical ground state beyond n = 12, 23 which corroborates our predictions from BS-UKS DFT as well as those previously reported by Malrieu et al 29 In light of multi-reference calculations, Mandado et al demonstrated that anthracene and tetracene based PAHs do not exhibit anti-ohmic behavior in their ground state but do in some of the lowest energy excited states.…”
Section: Discussionmentioning
confidence: 60%
“…This is well reflected from the 〈 S 2 〉 BS values (Table S5 in ESI†) exceeding 1.0 from n = 8 onward, indicating the contribution from the components of higher spin multiplicities and hence reflecting the multi-configurational character. 29,76 The fractional occupation numbers of BS-UHF based natural orbitals (Table S7 of ESI†) used to compute the radicaloid character, further support the idea of tetra-radical character, with four nearly singly occupied open shells from n = 11 onwards. A DMRG study by Chan et al also established the singlet diradical ground state with the plausible evolution of polyradical ground state beyond n = 12, 23 which corroborates our predictions from BS-UKS DFT as well as those previously reported by Malrieu et al 29 In light of multi-reference calculations, Mandado et al demonstrated that anthracene and tetracene based PAHs do not exhibit anti-ohmic behavior in their ground state but do in some of the lowest energy excited states.…”
Section: Discussionmentioning
confidence: 60%
“…As these systems can in principle be subject to a Jahn–Teller effect, removing the HOMO–LUMO degeneracy, they can regress to closed-shell or standard diradicaloid character. However, from old studies of Chichibabin series and other works, one knows that aromaticity in six-membered rings objects to the pairing of unpaired electrons, which may counteract the above Jahn–Teller effect. The present work will exploit this physical effect in designing candidate molecules, which, should they exist, would represent a new class of diradicals that we propose to name entangled diradicals, as opposed to disjoint diradicals.…”
Section: Brief Recall On Singlet Diradicalsmentioning
confidence: 99%